2002
DOI: 10.1002/cncr.10291
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of the activity concentration ratio of red marrow to blood and implications for red marrow dosimetry

Abstract: BACKGROUND The method for red marrow dosimetry in radioimmunotherapy, in the absence of specific activity uptake in red marrow, is based on the activity measured in the blood or plasma. The activity concentration ratio of red marrow to blood is then assumed to be constant. The aim of the current study was to determine whether this ratio varies with time after injection. METHODS Measurements were carried out with both animals and patients.Tumor‐bearing rats were intravenously injected with iodine‐131–, iodine‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The absorbed dose to the bone marrow was calculated using a bone marrow-to-serum activity concentration ratio valid for macromolecules (0.19), because chromatography indicated that most (.80%) of the 211 At in serum was bound to the antibody fragments. The ratio corresponds to a bone marrowto-blood ratio of 0.32, a value in the range of what has been observed in previous radioimmunotherapy studies (33).…”
Section: Discussionmentioning
confidence: 61%
“…The absorbed dose to the bone marrow was calculated using a bone marrow-to-serum activity concentration ratio valid for macromolecules (0.19), because chromatography indicated that most (.80%) of the 211 At in serum was bound to the antibody fragments. The ratio corresponds to a bone marrowto-blood ratio of 0.32, a value in the range of what has been observed in previous radioimmunotherapy studies (33).…”
Section: Discussionmentioning
confidence: 61%
“…In this study, values of Drm were found to be between 60% and 70% of Dwb, which is reasonable considering the modest 350 contribution of the self-absorbed dose and the values for the Swb←wb/Srm←wb ratio. In patients in whom there is red-marrow and/or bone uptake, it is generally recommended to use imagingbased estimates of Drm 26,36,37 , as blood-based values may underestimate the real value.…”
Section: Discussionmentioning
confidence: 99%
“…The full expressions of self-dose and cross-dose contribution to the RM can be obtained by substituting Equations 2, 3, and 4 into Equation 6. By introducing a mass scaling for the S factors in Equation 6, the m WB 2 patient terms cancel out and a patient mass-independent term remains, whereas the final cross RM dose term will be patient massdependent.…”
Section: Rm Dose-estimation Methodsmentioning
confidence: 99%